Comparative Randomized Study of Tolerability, Reactogenicity, Immunogenicity and Safety of the Vaccine «BiVac Polio» (Oral Poliovirus Vaccine Type 1,3) - Yu. H. Khapchaev; O. E. Ivanova; M. F. Vorovitch; V. V. Romanenko; A. E. Makarov; S. G. Drozdov; A. A. Ishmukhametov (Эпидемиология и вакцинопрофилактика)
Through the use of trivalent oral poliovirus vaccine made from Sabin strains of types 1, 2, 3 (tOPV), outstanding success of Global polio eradication program has been achieved. Since 1999, wild polio virus type 2 does not circulate in the world. To enhance immunity to poliovirus types 1 and 3, to reduce the risk associated with the continued use of tOPV (forming of vaccine-derived polioviruses and the emergence of cases of post-vaccination complications), the WHO proposed its replacement with bivalent oral poliovirus vaccine (bOPV) in programs of mass immunization. The results of clinical studies of tolerability, reactogenicity, safety and immunological effectiveness of the bOPV «BiVac Polio» developed in Chumakov Federal Scientific Center for Research and Development of Immune-and Biological Products of Russian Academy of Sciences are presented. «BiVac Polio» is a preparation of Sabin strains of polio virus type 1 (strain LSc 2ab) and type 3 (strain Leon 12a1b). The content of infectious viral units per vaccination dose is not less than 106 0 TCD50 for poliovirus type 1 and not less than 1055 TCD50 for poliovirus type 3. As a preparation of comparison, trivalent oral poliovirus vaccine from Sabin strains types 1, 2, 3 was used. The study included two stages. Comparative assessment of tolerability, reactogenicity and safety of the vaccine «BiVac Polio» and tOPV was the purpose of the first stage which included 20 adults of both sexes. At the second phase of the study, a comparative investigation of tolerability, safety and immunogenicity of the vaccine«BiVac Polio» and tOPV in children aged 18 months and 6 months was carried out (each group consisted of 60 children). Estimation of vaccine immunogenicity was carried out using the level of seroconversion - rise of neutralizing antibody titers in the sera of recipients taken before and 28 days after vaccination. The titer of neutralizing antibodies in the blood serum to poliovirus type 1 and 3 was determined by microneutralization assay on HEp-2 cells. The results of clinical studies have shown that in their basic characteristics, «BiVac Polio» vaccine is not inferior to the preparation of comparison (tOPV) and may be used for prophylaxis of poliomyelitis.